Telemedicine in home enteral nutrition: a structured survey exploring acceptability, preferences and experiences among patients - Ya Ma; Xuemei Li; Qian You; Wen Hu; Zhiyong Rao; Yanru Deng; Yiyao Zhang; Lei Shi (BMC Health Services Research)
Abstract Background Given that Telemedicine are widespread in China, and we have developed home enteral nutrition service with telemedicine (HENST) to satisfy HEN requirement of patients. However, only little is known about patient’s experience of HENST model. The objective of this interview study was to explore patient’s experiences and improvement direction of the HENST model. Methods The revisit station of HEN patients between 2018 and 2022 were counted. And epidemiological characteristics of HENST patients in 2022 were collected. Meanwhile, the structured survey was conducted to collect experiences about HENST model from part HEN patients in 2022. Results The revisit rate of HEN patients increased from 25.8% to 35.8%, and the major revisit approach changed from face-to-face clinic visits to HENST. Overall, 1437 HENST patients with 3710 visit records in 2022. Median age was 58.0 years, and most patients were from Chengdu (61.3%). For interview subjects, distance and expense from home to hospital for HENST patients were more than those for face-to-face clinic visit patients, illustrating that HENST can save time and expenses. The patient satisfaction rate for HENST was 98.7%, and viewpoints of HENST improve the visit experience have been deemed by majority HENST patients (81.8%). For face-to-face clinic visit patients, prefer to face-to-face communication was the main reason why not choose HENST. Conclusions HENST is a economic beneficial visit model, with high satisfaction. We should optimize and promote existing video call function of this platform to meet the demands of face-to-face communication. Trial registration The study was registered in the Chinese Clinical Trial Registry (clinical registration number: ChiCTR2100053762, registration date: 2021–11-29).